Cultural Fusion: The Impact of K-Pop on the Indonesian Perspectives and Identities: English - Masada, Deviana Gloria (Jurnal Sentris, 2024)
The growth of the South Korean entertainment sector, particularly K-Pop, has had a big influence on Indonesian identity and worldview. With its distinctive dance, music, fashion, and fan culture, K-Pop has shaped Indonesia's younger generation and allowed for a shift in cultural preferences and ways of thinking. The purpose of this research is to examine how K-Pop has influenced Indonesian identities and viewpoints. This study clarifies how Indonesians' perceptions of music, fashion, and other popular culture have been impacted by K-Pop's widespread appeal. The diversity of music and fashion styles in Indonesia is also enhanced and broadened by the influence of K-Pop. But there has also been some discussion over how K-Pop has influenced Indonesian identity. According to certain viewpoints, K-Pop's influence may change local preferences and threaten Indonesia's cultural identity. On the other hand, some perspectives see K-Pop's influence as a type of cultural globalization that can deepen and expand knowledge and appreciation of South Korean culture. Keyword: K-Pop, Perspectives and Identities, Culture